Demand Theory and Empirical Demand Curves - Dan Usher (Queen's University, Department of Economics, 1970)
This paper talks about the empirical demand theory as described in the textbooks as well as the one estimated in econometric work. Thus, the argument of this paper is that the gulf between the theory of demand as described in textbooks and the procedure followed in estimating demand curves is wider than need be, that a theory of demand can be formulated about the variables used in practice, that the grounds for supporting demand curves are downward sloping are at least as strong in the new theory as in the old one, and that the new theory is more efficiently connected to empirical evidence.
Keywords: 330